Hydraulic Capacity Analysis and Design of Road Culvert Drainage for Spillway Outflow in an Industrial Area in Pekalongan, Central Java, Indonesia - Miskar Maini (G-Tech: Jurnal Teknologi Terapan, 2026)
The development of industrial areas significantly increases surface runoff by expanding impervious surfaces, potentially exceeding the capacity of existing drainage systems and increasing flood risk. In many industrial zones, stormwater management infrastructure must also accommodate additional discharge from retention pond spillways, which can further burden road drainage systems. In the study area, spillway outflow from a retention pond is conveyed into the road drainage network, requiring an adequately designed culvert system to accommodate the flow safely. This study aims to analyze the hydraulic capacity and design an appropriate road culvert drainage system to convey spillway outflow in an industrial area. Secondary data on design flood discharge were obtained from previous studies that conducted rainfall frequency analysis, flood discharge estimation using the Nakayasu Synthetic Unit Hydrograph method, and spillway routing analysis. The results show that the design flood discharge for the 100-year return period (Q100) is 8.68 m³/s. A hydraulic analysis using the Manning equation was performed to determine the culvert dimensions required to convey the design discharge safely. The analysis indicates that the proposed culvert system is hydraulically adequate. A culvert with a diameter of 2.0 m is installed in the upstream section to accommodate concentrated inflow from the spillway outlet. In comparison, two parallel culverts with a diameter of 1.3 m are installed along the middle-to-downstream sections on both sides of the road. This configuration provides a total discharge capacity of 8.752 m³/s, exceeding the design flood discharge. The results demonstrate that the proposed design improves drainage Reliability in industrial areas and contributes to flood mitigation by regulating runoff discharge, thereby reducing potential flood risk in downstream residential areas. These findings provide practical guidance for infrastructure planning and policy strategies to integrate industrial drainage systems with regional flood mitigation efforts.